Advertising and a Democratic Press - C. Edwin Baker (Princeton University Press, 2014)
T ARGUE in this book that advertising seriously distorts and diminishes the mass media's contribution to a free and democratic society—and then consider policy responses. Here I want to respond to two possible reasons for doubting the practical relevance of such an argument. First, folk wisdom holds: "If it ain't broke, don't fix it." Thus, when I argue for government interventions, for "repairs," that would affect press production, it is worth wondering whether my exercise is not best ignored— or even more wisely, emphatically rejected. Our press, or at least its print media, is respected around the world. Moreover, history is filled with recurrent instances of various governments censoring the press— often with their interventions justified in good faith as purportedly promoting the public good. But time after time these arguments and the resulting censorship were seen in retrospect to have been misguided. Caution recommends a firm stand against proposals for government intervention. This caution is especially wise if the press is basically OK, even though surely each of us has a few complaints and would prefer a slightly different press. As I await the early edition of the next day's New York Times each night at the newsstand, I have an almost reflexive reaction: "This isn't perfect but it is quite informative; surely, we've got it pretty good with respect to the press." Although there are always problems and lapses, the modern American press provides more and better information to the public than any previous institution. This impressive even if imperfect press arguably exists precisely because of its freedom from government restraint, freedom constitutionally guaranteed in this country. Any attempt by government to impose, for example, requirements of press responsibility would result in a loss of valuable freedom—this last point being central to First Amendment doctrine that I fully support.